Exploring the relationship between soil and plant evolutionary diversity in the Roraima table mountain OCBIL, Guayana Highlands. (2nd March 2021) - Campos, Prímula Viana; Schaefer, Carlos Ernesto G R; Pontara, Vanessa; Senra, Eduardo Osório; Viana, Pedro Lage; Oliveira, Fábio Soares; Candido, Hugo Galvão; Villa, Pedro Manuel
Abstract: OCBIL theory aims to develop hypotheses that explain the evolutionary ecology of biota on old, climatically buffered, infertile landscapes (OCBILs). The table mountain OCBILs of the Guayana Highlands are a major centre of Neotropical plant diversity; however, knowledge about the underlying mechanisms of plant community assembly at the mountaintops is still limited. We evaluated the effect of a fine-scale geoenvironmental gradient on the phylogenetic metrics of plant communities on the iconic, highly isolated Roraima table mountain of the Guayana Highlands. We selected three specific geoenvironments: Bonnetia -shrubby rupestrian grassland, peaty rupestrian grassland and sandy rupestrian grassland. We evaluated evolutionary history using species richness and phylogenetic metrics and analysed effects of the soil on phylogenetic metrics using linear models. Of the 55 species surveyed, 40% are endemic to the Guayana Highlands. Bonnetia -shrubby rupestrian grassland showed higher species richness (47) than peaty rupestrian grassland (30) and sandy rupestrian grassland (24). We observed significant differences in phylogenetic diversity and structure among geoenvironments. The highest phylogenetic diversity was found for Bonnetia -shrubby rupestrian grassland and sandy rupestrian grassland. Peaty rupestrian grassland had significantly lower mean pairwise phylogenetic distance and all standardized phylogenetic metrics. The values of standardized phylogenetic metrics were close to zero, suggesting random phylogenetic structure. The linear models revealed that soil texture explained most of the variation in phylogenetic metrics. Our results might be related to the long geological history of tepuis and the accumulation of lineages over tens of millions of years, which supports the OCBIL theory.